The lexical access of multiple words during a single fixation: overlapping access processes? - Wakeford, Laura J.; Murray, Wayne S. (Language, Cognition & Neuroscience, 2020)
Since it has become increasingly difficult to tease apart the predictions of serial and parallel models of eye movement control during reading, we return to the underlying theoretical question of whether parallel lexical processing of two words is, at the very least, psychologically plausible. Two horizontally aligned letter strings were presented simultaneously on a screen, the task being to decide whether they were physically identical or not. Even with presentation durations short enough to prohibit serial inspection of each word, the results show clear lexical effects: high frequency word pairs were responded to faster and with fewer errors than low frequency words. Effects of lexicality, orthography and scanning direction were also found. The results suggest that two words can be processed at a lexical level in an overlapping fashion.